PENGARUH TEMPORARY DIFFERENCE, PERMANENT DIFFERENCE, DAN LEVERAGE TERHADAP PERTUMBUHAN LABA DENGAN SMALL AND LARGE BOOK TAX DIFFERENCE SEBAGAI PEMODERASI - Umi Nur Arofah, 13.05.52.0075; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
Book Tax Difference occurs because there is a difference between financial reporting and tax reporting in terms of accounting principles, accounting methods and procedures, income and expense recognition, and income and expense treatment. Due to the emergence of the difference will lead to profit growth will increase or decrease. While leverage aims to steer the extent to which debt is used in the company. Profit growth may be affected by the components referring to PSAK 46 regarding income tax and IAS 12 on income tax ie deferred tax due to temporary taxable difference. The purpose of this research is to know temporary, permanent difference and leverage to profit growth with small and large book tax differences as moderator. With the sample of research is manufacturing company Food and Beverage sector, as many as 20 manufacturing companies listing on BEI in 2012 until 2016. Data analysis using moderate analysis regression with the base of absolute difference .. The results showed that temporary differences and leverage have a significant positive effect on profit growth. permanent difference has a significant negative effect on profit growth. small and large book tax differences is a moderating variable.Keywords: Temporary difference, permanent difference, leverage, small and large book tax differences, profit growth